¿Casada o viuda? El abandono del hogar en el Burgos de mediados del siglo XVIII - Sainz de la Higuera, Francisco J. (Huarte de San Juan. Geografía e Historia, 2006)
1% of the household in Burgos, women didn’t’t know if they were married or they belong to the long-suffering collective of widowers. Completely alone, in company of their children or under the protection of any close relative, these women face the existence, with their husband in unknown where about, abandoned, poor, crowded together in small, narrow and unhealthy flats, with modest economies and as unskilled workers. ¿What reason explained the man’s absence in their beds?